2011
DOI: 10.22610/jebs.v3i4.279
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationship between Military Expenditure and External Debt: Patterns of Causation in Northern Africa Countries

Abstract: It is supported by academics and scholars that defense expenditure can significantly affect a country's economic growth and in some cases it influences external debt having implications in various macroeconomic indicators. However, relevant empirical studies have produced contradictory evidence while the literature in this field remains relatively poor. In this spirit, this survey investigates the causal links between military expenditure and external debt for four emerging Northern Africa countries (i.e. Egyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Empirical results show that military spending strongly affects a country's external debt. These are the only results provided by this study that validate the hypothesis that the military burden may be important in determining the evolution of debt in developing countries (Georgantopoulos 2011).…”
Section: Literature Reviewsupporting
confidence: 80%
See 2 more Smart Citations
“…Empirical results show that military spending strongly affects a country's external debt. These are the only results provided by this study that validate the hypothesis that the military burden may be important in determining the evolution of debt in developing countries (Georgantopoulos 2011).…”
Section: Literature Reviewsupporting
confidence: 80%
“…This study (Georgantopoulos 2011) examines the causal links between military spending and external debt of four emerging countries in North Africa (i.e. Egypt, Tunisia, Algeria, and Morocco) during the period 1988-2009.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The democratic government has more stability in military spending than the other. Some empirical studies indicated that military expenditure doesn't affect external debt, but this cannot be generalized to all countries as the outcome will differ between countries (Georgantopoulos & Tsamis, 2011). Mangır and Kabaklarlı (2016) indicate that military expenditure is neither good nor bad for the economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found no evidence that military burden had any impact on the evolution of debt in Argentina and Brazil, but some evidence that military burden tended to increase debt in Chile. Georgantopoulos and Tsamis (2011), using a cointegration test, investigated the causality between defence spending and external debt for four emerging Northern Africa countries (Morocco, Algeria, Tunisia and Egypt) during the period 1988-2009.…”
Section: Literature Reviewmentioning
confidence: 99%